The relationships among attachment style, willingness to express negative emotion, and social anxiety in young adults. - Torrecampo, Ana Patricia (2014.)
The purpose of the current study was to examine the relationships among attachment style, willingness to express negative emotion, and social anxiety. A survey was done to examine the relationship of these variables. There is a difference on young adults? willingness to express negative emotion at different attachment categories. Social anxiety is not associated with willingness to express negative emotion. There is a difference on the levels of social anxiety at different attachment categories
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2014.
Keywords: Young adults -- charactesristics -- Reseach